(untitled) (CIPEEX, 2025)
Autism Spectrum Disorder (ASD) is characterized by deficits in neuropsychomotor development, affecting cognition, communication, and social interaction, as well as manifesting restricted interests and repetitive behaviors, in addition to patterns of food selectivity and compulsive eating. The present study aims to evaluate the prevalence and profile of selectivity and compulsive eating disorders in autistic children, correlating them with anthropometric parameters and child growth curves. This is a cross-sectional, quantitative, descriptive, and observational study based on the analysis of a questionnaire applied to children assisted at the Association of Exceptional Parents and Friends (APAE) in the municipality of Anápolis. The research revealed that a significant number of children have food rituals. Moreover, selectivity was observed, particularly regarding food texture, and a preference for eating without permission at inappropriate times. Anthropometric data analysis indicated that 15.4% of the children had very short stature, and 21.7% were classified as overweight. Regarding Body Mass Index (BMI), among children aged 0 to 5 years, 33.3% were obese, and among those aged 5 to 20 years, 17.6% were overweight. The results highlight the significant relationship between ASD and feeding disorders, emphasizing the need for interventions to improve the nutritional health of these children, which is fundamental for their growth and healthy development. The analysis of feeding behavior in children with ASD is, therefore, a crucial field of study.